Pelatihan Desain Grafis Untuk Guru SMP Negeri 3 Mendo Barat Bangka - Sidhiq Andriyanto; Ahmat Josi (Madani : Indonesian Journal of Civil Society, 2021)
This community service activity aims to provide graphic design training for teachers. Through graphic design training, it is hoped that it can provide many benefits to teachers to add skills and present innovative and attractive learning media. This community service activity begins with a survey to partner locations, planning activities, compiling training materials, then implementing training. This activity was held at SMP Negeri 3 Mendo Barat, Bangka. The time for this training is two days. The result of this community service activity was graphic design training for teachers which went well with the improvement of skills in the field of information technology.